A rare pediatric case of pedunculated cardiac hemangioma of the left ventricle. Issue 10 (16th July 2022) - Arora, Vasundhara; Verma, Mansi; Malhi, Amarinder S.; Devagourou, Velayoudam; Arava, Sudheer; Jagia, Priya
Abstract: A 12‐year‐old male child with atypical chest pain and fatigue since past 3 months underwent cardiac magnetic resonance (CMR) imaging for suspicious globular mobile mass detected in the left ventricle on a transthoracic echocardiography. CMR revealed peripheral vascular blush on the first pass perfusion images with centripetal progressive intensely bright enhancement on late gadolinium‐enhanced images. Further confirmation and histological diagnosis of the tumor was made through transaortic aortic resection of the mass.